2011
DOI: 10.1089/brain.2011.0036
|View full text |Cite
|
Sign up to set email alerts
|

A Sliding Time-Window ICA Reveals Spatial Variability of the Default Mode Network in Time

Abstract: Recent evidence on resting-state networks in functional (connectivity) magnetic resonance imaging (fcMRI) suggests that there may be significant spatial variability of activity foci over time. This study used a sliding time window approach with the spatial domain-independent component analysis (SliTICA) to detect spatial maps of resting-state networks over time. The study hypothesis was that the spatial distribution of a functionally connected network would present marked variability over time. The spatial sta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

12
209
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
10

Relationship

3
7

Authors

Journals

citations
Cited by 243 publications
(224 citation statements)
references
References 45 publications
12
209
0
Order By: Relevance
“…Standard stationary FC analyses assume temporal stationarity and are blind to the temporal evolution of FC. Several recent studies have since confirmed the non-stationarity of FC (Handwerker et al, 2012;Hutchison et al, in press;Kang et al, 2011;Kiviniemi et al, 2011;Li et al, in press;Majeed et al, 2011). We will use the terms dynamic FC to specifically refer to fluctuating connectivity during rest, and stationary FC to refer to connectivity estimated under the assumption of temporal stationarity.…”
Section: Introductionmentioning
confidence: 99%
“…Standard stationary FC analyses assume temporal stationarity and are blind to the temporal evolution of FC. Several recent studies have since confirmed the non-stationarity of FC (Handwerker et al, 2012;Hutchison et al, in press;Kang et al, 2011;Kiviniemi et al, 2011;Li et al, in press;Majeed et al, 2011). We will use the terms dynamic FC to specifically refer to fluctuating connectivity during rest, and stationary FC to refer to connectivity estimated under the assumption of temporal stationarity.…”
Section: Introductionmentioning
confidence: 99%
“…This evidence led to the introduction of a new concept in evaluating brain regions connectivity named dynamic FC which has encouraged the introduction of a large number of methods to detect it. Sliding window, for instance, has been a widely used method to assess dynamic FC [12][13][14][15][16]. Dynamic connectivity regression (DCR) is another method recommended by [4,5] to discover FC change points between brain areas.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, many recent studies have emphasized the importance of treating FC as a dynamical quantity, that is, evolving in time (Hutchison et al 2013;Park and Friston 2013). Different tools have been proposed to introduce temporal variations into the analyses of FC, such as sliding windows (Sakoglu et al 2010;Bassett et al 2011;Jones et al 2012;Shirer et al 2012;Allen et al 2012;Handwerker et al 2012), dynamic conditional correlation (Lindquist et al 2014), single-volume co-activation patterns (CAPs) (Tagliazucchi et al 2012;Liu and Duyn 2013;Amico et al 2014), as well as a combination of sliding windows and other methods, such as Independent Component Analysis (Kiviniemi et al 2011) or Principal Component Analysis (Leonardi et al 2013). For a review of these methods, see (Hutchison et al 2013).…”
Section: Introductionmentioning
confidence: 99%